Holding on - Lee, Sophia N. (Atheneum Books for Young Readers, 2022)
young girl spends song-filled summers with her music-loving grandmother in the Philippines, but when her beloved Lola starts slipping into silence and stillness, the girl helps her grandmother hold on with music and the joyful memories the songs bring.